2003
DOI: 10.1124/mol.63.3.690
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Inhibition of Tumor Necrosis Factor α Production Induced by Amyloidogenic C-Terminal Peptide of Alzheimer's Amyloid Precursor Protein in Macrophages: Involvement of Multiple Intracellular Pathways and Cyclic AMP Response Element Binding Protein

Abstract: In the present study, we focused on the molecular events involved in tumor necrosis factor-␣ (TNF-␣) production in response to the amyloidogenic 105-amino acid carboxyl-terminal fragment (CT105) of amyloid precursor protein, a candidate alternative toxic element in Alzheimer's disease pathology, and the mechanisms by which cyclic AMP regulates the relating inflammatory signal cascades. CT105 at nanomolar concentrations strongly activated multiple signaling pathways involving tyrosine kinase-dependent extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…Our results clearly show that, whereas adrenergic stimulation-mediated suppression involves protein kinase A and thus cAMP production, IL-10 suppression of TNF-␣ does not. Furthermore, previous studies have demonstrated that dibutyryl cAMP inhibits TNF-␣ synthesis and that this involves the cAMP response element binding protein and interference of the NF-B nuclear signaling pathway (7,27,29). In contrast, cellular mechanisms by which IL-10 has been shown to inhibit TNF-␣ production are more diverse.…”
Section: Discussionmentioning
confidence: 84%
“…Our results clearly show that, whereas adrenergic stimulation-mediated suppression involves protein kinase A and thus cAMP production, IL-10 suppression of TNF-␣ does not. Furthermore, previous studies have demonstrated that dibutyryl cAMP inhibits TNF-␣ synthesis and that this involves the cAMP response element binding protein and interference of the NF-B nuclear signaling pathway (7,27,29). In contrast, cellular mechanisms by which IL-10 has been shown to inhibit TNF-␣ production are more diverse.…”
Section: Discussionmentioning
confidence: 84%
“…Since cAMP could activate the ERK kinase activity and inhibit the p38 kinase activity [10,11,25] , we next examined whether cAMP regulated the kinase activity of MAPK members in Hep3B cells. Treatment of Hep3B cells with 8-bromo-cAMP dose dependently suppressed p38 phosphorylation and this effect was reversed by pretreatment with Rp-cAMPS ( Figure 3B(a)).…”
Section: Involvement Of Camp In the Regulation Of Facl4 Gene Expressimentioning
confidence: 99%
“…A previous study demonstrated that an elevated cAMP could suppress the N-formyl methionylleucyl-phenylalanine-induced p38 mitogen-activated protein kinase (MAPK) activation in the hypertonic stress suppression of neutrophil function [10] . Another experiment indicated that cAMP could inhibit multiple signaling pathways, including p38, induced by an amyloid precursor protein in human monocytic cell line THP-1 [11] . These findings suggested a link between elevation of cAMP and inhibition of p38 activation.…”
Section: Introductionmentioning
confidence: 99%
“…For unlabeled in vitro immune complex kinase assays, control IgG or CDK1-B1 protein complex was incubated with 0.5 g of His-CREB WT or His-CREB S270A/S271A in the presence of 100 M ATP as described above. Binding reaction mixtures (20 l), containing in vitro labeled His-CREB WT or CREB S270A/S271A , 2 g of poly(dI-dC), and 32 P-labeled probe in binding buffer (4 mM HEPES, pH 7.9, 1 mM MgCl 2 , 0.5 mM dithiothreitol, 2% glycerol, and 20 mM NaCl), were incubated for 30 min at room temperature (37). The protein-DNA complexes were separated on 4% nondenaturing polyacrylamide gels in 0.25ϫ Tris borate/ EDTA buffer and were autoradiographed as described in Ref.…”
Section: Methodsmentioning
confidence: 99%